Appropriate Risk Stratification and Accounting for Age-Adjusted Reciprocal Changes in the Thoracolumbar Spine Reduces the Incidence and Magnitude of Distal Junctional Kyphosis in Cervical Deformity Surgery. Issue 21 (1st November 2021) - Passias, Peter G.; Bortz, Cole; Pierce, Katherine E.; Kummer, Nicholas A.; Lafage, Renaud; Diebo, Bassel G.; Line, Breton G; Lafage, Virginie; Burton, Douglas C.; Klineberg, Eric O.; Kim, Han Jo; Daniels, Alan H.; et al.
Abstract : Study Design: Retrospective cohort study of a prospective cervical deformity (CD) database. Objective: Identify factors associated with distal junctional kyphosis (DJK); assess differences across DJK types. Summary of Background Data: DJK may develop as compensation for mal-correction of sagittal deformity in the thoracic curve. There is limited understanding of DJK drivers, especially for different DJK types. Methods: Included: patients with pre- and postoperative clinical/radiographic data. Excluded: patients with previous fusion to L5 or below. DJK was defined per surgeon note or DJK angle (kyphosis from LIV to LIV-2)<-10°, and pre- to postoperative change in DJK angle by<-10°. Age-specific target LL-TK alignment was calculated as published. Offset from target LL-TK was correlated to DJK magnitude and inclination. DJK types: severe (DJK<−20°), progressive (DJK increase>4.4°), symptomatic (reoperation or published disability thresholds of NDI ≥ 24 or mJOA⩽14). Random forest identified factors associated with DJK. Means comparison tests assessed differences. Results: Included: 136 CD patients (61 ± 10 yr, 61%F). DJK rate was 30%. Postop offset from ideal LL-TK correlated with greater DJK angle (r = 0.428) and inclination of the distal end of the fusion construct (r = 0.244, both P  < 0.02). Seven of the top 15 factors associated with DJK were radiographic, four surgical, and four clinical. Breakdown by type: severe (22%), progressive (24%), symptomatic (61%). Symptomatic had more posterior osteotomies than asymptomatic ( P  = 0.018). Severe had worse NDI and upper-cervical deformity (CL, C2 slope, C0-C2), as well as more posterior osteotomies than nonsevere (all P  < 0.01). Progressive had greater malalignment both globally and in the cervical spine (all P  < 0.03) than static. Each type had varying associated factors. Conclusion: Offset from age-specific alignment is associated with greater DJK and more anterior distal construct inclination, suggesting DJK may develop due to inappropriate realignment. Preoperative clinical and radiographic factors are associated with symptomatic and progressive DJK, suggesting the need for preoperative risk stratification. Level of Evidence: 3 Abstract : Distal junctional kyphosis (DJK) may develop as compensation for deformity in the thoracic curve. This study identified significant radiographic, surgical, and clinical factors associated with severe, progressive, and symptomatic DJK. Meeting appropriate alignment goals or stratifying preoperative risk may realize a reduction in DJK instance.